2015
DOI: 10.1371/journal.pcbi.1004622
|View full text |Cite
|
Sign up to set email alerts
|

Tamping Ramping: Algorithmic, Implementational, and Computational Explanations of Phasic Dopamine Signals in the Accumbens

Abstract: Substantial evidence suggests that the phasic activity of dopamine neurons represents reinforcement learning’s temporal difference prediction error. However, recent reports of ramp-like increases in dopamine concentration in the striatum when animals are about to act, or are about to reach rewards, appear to pose a challenge to established thinking. This is because the implied activity is persistently predictable by preceding stimuli, and so cannot arise as this sort of prediction error. Here, we explore three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 130 publications
0
43
1
Order By: Relevance
“…This time course suggests that prediction error signals reflect the evolving decision process. Given the dense dopaminergic projections to brain regions involved in decision making [48], the early dopamine prediction errors might even be able to influence the current choice computation, for instance by modulating the gain of evidence accumulation [49]. Alternatively, pre-decision dopamine responses do not impact choices directly but other aspects of immediate behavior such as the willingness to complete the trial [50].…”
Section: Discussionmentioning
confidence: 99%
“…This time course suggests that prediction error signals reflect the evolving decision process. Given the dense dopaminergic projections to brain regions involved in decision making [48], the early dopamine prediction errors might even be able to influence the current choice computation, for instance by modulating the gain of evidence accumulation [49]. Alternatively, pre-decision dopamine responses do not impact choices directly but other aspects of immediate behavior such as the willingness to complete the trial [50].…”
Section: Discussionmentioning
confidence: 99%
“…Under many conditions, however, it has been difficult to disambiguate whether dopamine represents RPE or value. First, a dopamine ramp can occur regardless of whether dopamine represents value or RPEs (Gershman, 2014;Lloyd and Dayan, 2015;Morita and Kato, 2014). For instance, a theoretical study showed that the shape of the value function matters: if the value function is a convex function of proximity to reward, a TD RPE can exhibit a positive ramp (Gershman, 2014) (more general conditions are described in the Supplementary Note; see also Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These ramping signals could not be interpreted as phasic activity elicited by prediction error or as tonic background activity, given correspondence to a specific, prolonged epoch of goal pursuit and resolution. This signal has been proposed to be “quasi-tonic” (Lloyd and Dayan, 2015): like tonic DA, ramping DA might operate via extrasynaptic, background firing, but this remains to be comprehensively characterized. In contrast, phasic DA primarily operates via synaptic release (Floresco et al, 2003).…”
mentioning
confidence: 99%
“…This ramping dynamic has been observed in rodents traversing a maze towards a reward but also while anticipating a highly-uncertain reward (i.e., 50% reward probability (Fiorillo et al, 2003; Gershman, 2014)) suggested that ramping may reflect averaged activity elicited by reward prediction errors. Evidence from computational models suggests that DA ramps may feasibly support multiple functions: (1) resolution of action timing uncertainty; (2) increasing gain control for a chosen action; and (3) a discounted function of vigor (Lloyd and Dayan, 2015). Importantly, these functions are proposed to be non-mutually exclusive: ramping activity may reflect multiple functions at any given time.…”
mentioning
confidence: 99%